SATIRIC ELEMENTS IN TRADITION AND CULTURAL ROOTLESSNESS ARE DEPICTED IN CYNTHIA OZICK’S BLOODSHED AND THREE NOVELLAS - S., Sanju; Silvest, R. S. Regin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Judaism has a strong hold on the concept of Jewishness, and its connection with the fundamental goodness of life and humans is what Jewishness is all about. It is because of this emphasis on the human race’s kinship, the sanctity of human life and personality, and the individual’s right to freedom that Jews have been able to not only endure the suffering inflicted upon them but also, be empowered to celebrate who they are. Jewish rites are extended into everyday life by Ozick. Cynthia Ozick’s Bloodshed and Three Novellas, is mostly focused on the tradition’s betrayal. Each tale in the anthology reflects extensively on tradition, on the betrayal of Jewish identity, and illustrates the unfavorable effects of rejecting traditional values. All of the main characters recognize how important it is to acknowledge their Jewishness in order to promote harmony, wellness, and peace. Ozick makes a strong statement on the challenges that Jews experience in assimilating into American culture. By emphasizing on numerous imperfections and flaws in the personality of her characters, she brings out funny situations and thoughts.